Prevalence of periodontitis and its association with smokeless tobacco (SLT) Use amongst the adult population of Greater Noida, India - A cross-sectional study - Simoona Athar; Sachit A Arora; Rupali Kalsi; Kumar Saurav; Vikram Arora; Kamal Baro (Indian Journal of Dental Research, 2022)
Context: Smokeless tobacco (SLT) has been consumed in India since times immemorial. It is the need of an hour to emphasise about awareness and harmful effects of SLT in relation to periodontium. Aim: The aim of the study was to access the prevalence of periodontitis and its association with SLT amongst the adult population of Greater Noida, India. Settings and Design: Hospital-based study and cross-sectional design. Methods and Material: This cross-sectional study included 512 SLT subjects between the ages of 18 and 79 years. The study was carried out from December 2019 to January 2022. A self-designed questionnaire was used for recording demographic details, forms of SLT, frequency, duration of use, and sites of retention of SLT products. The clinical periodontal parameters such as periodontal pocket depth (PPD) and clinical attachment level (CAL) were recorded in a given point of time. Statistical Analysis Used: Chi-square test and logistic regression analysis. Results: The prevalence of periodontitis among SLT was 81.6% with the highest occurrence of Stage III Periodontitis (35.4%). The use of SLT for ≥10 years [odds ratio (OR) = 3.05, 95% confidence interval (CI) 1.86–6.27] showed threefold the risk for periodontitis compared to others who consumed SLT for 4–5 years. Gutkha consumers [OR = 2.56 (95% CI = 0.75–3.48)] were 2.56 times more prone to have periodontitis as compared to other forms of SLT. Conclusions: Periodontitis is positively associated with SLT use. Awareness, timely intervention, and periodic screening in the SLT users will help to prevent the progression of periodontitis.